How to Optimize Local Government Supervision of Medical Waste Management in Healthcare Facilities? - Wahyati Yustina, Endang; Nurmardiansyah, Eko; Saraswati, Rika; Elwina Simandjuntak, Marcella (KnE Social Sciences, 2024)
Medical waste is classified as hazardous and toxic that causes environmental pollution and impacts public health. The management of this medical waste in healthcare facilities is under the supervision of multiple government bodies. However, the approach is not effective due to the overlapping regulations. This research proposes an effective solution for the supervision of medical waste in Indonesia. This is prescriptive qualitative research, and documentation studies are carried out by tracing relevant library sources. Field studies were conducted through online interviews equipped with focus group discussions (FGDs) to obtain complete data from the speakers, which were further analyzed using a qualitative approach. Regulations have existed, but the implementation has not been optimal, so there is still a lot of pollution due to medical waste that endangers public health. Optimization of local government supervision of medical waste needs to be carried out by enforcing regulations on medical waste. Local governments carry out preventive supervision through facilitation by providing infrastructure and guidance on medical waste management technology. The provision of sanctions for those who continue to violate the regulations is a form of repressive supervision so that public health is protected. Keywords: Surveillance; Local government; Medical waste; Health care facilities